2021
DOI: 10.35812/cellulosechemtechnol.2021.55.69
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cellulolytic Bacteria From Soil and Valorization of Different Lignocellulosic Wastes for Cellulase Production by Submerged Fermentation

Abstract: Cellulases are known to convert cellulose into monomeric or dimeric structures, hence playing an important role in bioethanol production, along with their applications in textile and paper industries. This study was directed towards the isolation and screening of cellulase producing bacteria from different soil samples on CMC (carboxymethyl cellulose) agar plates, followed by Gram’s iodine staining. Six strains showed clear zones of hydrolysis on CMC agar plates. Isolates were identified as Bacillus megaterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Regarding substrates, many studies frequently use raw (ligno-)cellulosic substrates as C-source instead of synthetic substrates, which can be preferable in the sense that these raw substrates are more representative of the inherent complexity of natural lignocellulosic materials. For instance, five species of Bacillus and Pseudomonas stutzeri showed maximum cellulase production using eucalyptus leaves as C-source among others such as corncob, sugarcane bagasse, rice husk, wheat straw, and seed pod of Bombax ceiba [ 60 ]. Similarly, the order of enzyme production using Bacillus subtilis strain with various substrates was sugarcane bagasse>wheat straw>rice husk, wheat bran>soybean meal>corncobs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding substrates, many studies frequently use raw (ligno-)cellulosic substrates as C-source instead of synthetic substrates, which can be preferable in the sense that these raw substrates are more representative of the inherent complexity of natural lignocellulosic materials. For instance, five species of Bacillus and Pseudomonas stutzeri showed maximum cellulase production using eucalyptus leaves as C-source among others such as corncob, sugarcane bagasse, rice husk, wheat straw, and seed pod of Bombax ceiba [ 60 ]. Similarly, the order of enzyme production using Bacillus subtilis strain with various substrates was sugarcane bagasse>wheat straw>rice husk, wheat bran>soybean meal>corncobs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this cluster, major representatives also belonged to Bacteroidota (Ohtaekwangia and Microscillaceae). Many representatives of Acidobacteriota (4), Actinobacteriota (Conexibacter, Galbitalea, Dactylosporangium, Iamia, and Solirubrobacter), Verrucomicrobiota (9), Myxococcota (9), Cyanobacteria (3), Chloroflexi (6), Bdellovibrionota (4), Spirochaeota (3), Planctomycetota (12), Crenarchaeota (4), Gemmatimonadota (1) and others appeared at this stage.…”
Section: Data Filteringmentioning
confidence: 99%
“…Soil from different environments can serve as a source of cellulolytic microorganisms. A number of studies focused on the isolation of single strains from various soil types [8][9][10][11][12], but this approach has several flaws. It was reported that cellulolytic bacteria may take up to a fifth part of the total soil community [13].…”
Section: Introductionmentioning
confidence: 99%
“…Soil from different environments can serve as a source of cellulolytic microorganisms. A number of studies focused on the isolation of single strains from various soil types [ 14 , 15 , 16 , 17 , 18 ], but this approach has several flaws. It was reported that cellulolytic bacteria may take up to a fifth of the total soil community [ 19 ].…”
Section: Introductionmentioning
confidence: 99%